School ICT resources, teachers, and online education: Evidence from school closures in Japan during the COVID-19 pandemic - Hideo Akabayashi; Shimpei Taguchi; Mirka Zvedelikova (Osaka University, Institute of Social and Economic Research (ISER), 2023)
As schools worldwide were forced to close due to the COVID-19 pandemic in early 2020, they struggled to switch to online education. Using Japan's nationwide administrative data, we examine the impact of schools' ICT equipment and teachers' IT skills on the provision of online classes, communication with students' families, and teachers' working hours during and shortly after the closures. To isolate supply-side effects, we exploit differences in ICT resources between public elementary and junior high schools using a municipality-level fixed effects model, the level at which ICT resources are decided. We find that basic ICT equipment was critical to implementing online classes, but IT skills were not. Furthermore, we observe no effect of ICT resources on schools' communication with families. However, IT skills were associated with teachers' working hours. In particular, weak IT skills resulted in a higher percentage of teachers working overtime.
Keywords: I20; J22; H75; 330; COVID-19; remote education; overtime work; teachers' skills; school resources